(3KeQI cdGe CHbQGW aj GdehdhOjf dKeGfjI CTgQs - (3YHO Gddg Hf GdWjH GdHZOGOj , nCoHh GdnanQL GHf GdpqWpqjH , J (B435 (3g` s
(3ChdgG (B:s
(3YQV HbQGW ai ebGdI ai GdehdhOjf dKeGfjI CTgQ Cf fJcde ai LejY GdCLfI hCjge jYjT hCjge dGjYjT JQLegG HGdehdhOjf dKeGfjI CTgQ s
(3BNQgG (B:s
(3JeJ ZQI cdGe HbQGW ai GdehdhOjf dKeGfjI CTgQ hGdMeO ddg QH GdYGdejf cKjQkG cESJMbGbI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3fSNI fajSI LOkGs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(888/1) s
Keywords: (3GdadSaI hGdefWbs